(untitled) (Revista Argentina de Cirugía, 2021)
Left-sided gallbladder (LSGB) is a rare bile duct abnormality, usually found during a cholecystectomy. Symptoms usually do not differ from those of a normally positioned gallbladder, making the preoperative diagnosis extremely uncommon. We report the case of an acute cholecystitis in a patient whit LSGB, safely managed with laparoscopic surgery. A 24-year-old male patient was admitted to our institution with clinical and radiological signs of acute cholecystitis. The intraoperative finding of an acute cholecystitis in a LSGB made us modify ports positioning and a cholangiograhy was done by direct puncture of the gallbladder before hilum dissection. After the cystic duct was identified, a transcystic cholangiography was performed which confirmed a complete and clear bile duct anatomy and laparoscopic cholecystectomy was safely completed. The intraoperative finding of a LSGB makes the surgeon change some aspects of the usual technique to perform a safe cholecystectomy as LSGB significantly increases the risk of common bile duct injuries. Meticulous dissection of the gallbladder hilum to achieve a critical view of safety and the systematic use of intraoperative cholangiography are extremely important to perform a safe laparoscopic cholecystectomy